Pediatric suppurative parotitis caused by Burkholderia pseudomallei - Fu,Zengzhen (2016)
Abstract Background: Suppurative parotitis caused by Burkholderia pseudomallei has been rarely found outside endemic areas. Case presentation: Herein, we report the recovery of Burkholderia pseudomallei from the pus of a suppurative parotitis observed in a 12-year-old boy who lived in Hainan province, China. Specimens of necrotic tissue were collected and sections were stained with hematoxylin and eosin. Pus sample was also collected for bacteriological examination. The suppurative inflammation was observed in the necrotic tissue section and Burkholderia pseudomallei were detected in the sample. Conclusion: In this adolescent, Burkholderia pseudomallei infection was present in the parotid, which consists of the first report of this bacterium in a parotitis case acquired in China.